(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
The financial sector requires dependable, expandable, and safe API framework solutions that enable seamless communication between customer facing applications and wellness systems. This paper discusses in detail a case study on the design and implementation of the Enterprise Application Programming Interface (EAPI) framework inside the Runtime Container (RTM) at Capital One. The EAPI framework has been designed to support commercial and retail banking users by providing efficient communication throughout a multi-layered service model of Proxy, Restful, and Integration Services. This paper will discuss, in detail, the complete software development lifecycle of creating new APIs, including gathering requirements, managing Agile projects, developing and deploying those new APIs into production across all Capital One locations using a structured approach for version control; continuous integration; and rigorous testing phases including JUnit automation; as well as managing Integration Service (IS) and Oracle Service Bus (OSB) components. The paper will also provide details about using monitoring tools such as Splunk to monitor the reliability of the systems. The methodology presented in this case study has proven the value of using a structured approach for creating API frameworks at large organizations; thus, establishing a blueprint and demonstrating improved efficiency for deploying large enterprise-wide API Frameworks in regulated industries